Personal characteristics of coffee consumers and non-consumers, reasons and preferences for foods eaten with coffee among adults from the Federal District, Brazil - Sousa, Alessandra Gaspar (2016)
The aim of this study is to describe the characteristics of consumers and non-consumers, the reasons and foods associated with coffee intake among adults from the Federal District, Brazil. This is a cross-sectional population-based survey conducted by telephone interview (n= 1,368). We collected information on detailed coffee intake, socio-demographic aspects and personal characteristics. The coffee had an average daily intake of 319 mL. Individuals were more likely to drink coffee at an older age (68%) and with higher body mass index (58%). The most cited reason for consuming coffee was the “personal pleasure” (48%), followed by “habit / tradition” of consuming coffee. Among non-consumers of this beverage, the main reason was not liking the taste and / or aroma of coffee (62%). The method of coffee preparation used was by infusion (86%) and sugar was the main sweetener used by 83% of consumers. The majority of consumers (59%) reported consuming coffee with certain foods such as bakery products. The results from our study may suggest that the popularity of coffee can be attributed to its taste, personal pleasure and habit, and the consumption is more likely to occur with the advance of age and with intake of other foods.